Investigation of Mill Balls Metal Deterioration in Mills KBM 370/850 (Sh-50А) when Fuel not Envisaged in the Mill Design is Used at Thermal Power Plants - Stepan Mysak; Taras Voronchak (Energy Engineering and Control Systems)
Method for determining mill balls metal deterioration rate in a ball mill KBM 370/850 (Sh-50А) of dust-system of coal-dust boilers TPP-210А and TPP-312 300МW of thermal power plants is described in the paper. The research is aimed at the development of the determination method of the mill balls deterioration rate in a ball mill, which would allow predicting the regulated refill of the ball mill by the mill balls. The research tasks were to analyze existing literature, to develop the calculation method of the mill balls deterioration rate in the mill, to carry out analytic calculations and obtain analytic relationships of mill balls deterioration rate, and based on this to develop generalized regularities for any dust-systems of thermal power plants. The rank of coal being grinded in the mill, the mill operation mode, design features of dust-system and boiler etc. influence the mill balls deterioration rate.